Neoparamoeba perurans n. sp., an agent of amoebic gill disease of Atlantic Salmon (Salmo salar) - Young, ND; Crosbie, PBB; Mark Adams; Barbara Nowak; Morrison, RN (2007)
Amoebic gill disease (AGD) is a potentially fatal disease of some marine fish. Two amphizoic amoebae Neoparamoeba pemaquidensis and Neoparamoeba branchiphila have been cultured from AGD-affected fish, yet it is not known if one or both are aetiological agents. Here, we PCR amplified the 18S rRNA gene of non-cultured, gill-derived (NCGD) amoebae from AGD-affected Atlantic salmon ( Salmo salar ) using N. pemaquidensis and N. branchiphila -specific oligonucleotides. Variability in PCR amplification led to comparisons of 18S rRNA and 28S rRNA gene sequences from NCGD and clonal cultured, gill-derived (CCGD) N. pemaquidensis and N. branchiphila . Phylogenetic analyses inferred from either 18S or 28S rRNA gene sequences unambiguously segregated a lineage consisting of NCGD amoebae from other members of the genus Neoparamoeba . Species-specific oligonucleotide probes that hybridise 18S rRNA were designed, validated and used to probe gill tissue from AGD-affected Atlantic salmon. The NCGD amoebae-specific probe bound AGD-associated amoebae while neither N. pemaquidensis nor N. branchiphila were associated with AGD-lesions. Together, these data indicate that NCGD amoebae are a new species, designated Neoparamoeba perurans n.sp. and this is the predominant aetiological agent of AGD of Atlantic salmon cultured in Tasmania, Australia.